Laparoscopic left hepatectomy in patients with intrahepatic duct stones and recurrent pyogenic cholangitis - Han, Sunjong (Korean J Hepatobiliary Pancreat Surg, 2012)
BACKGROUNDS/AIMS: Recently many studies have been reported the early results of a hepatectomy for various intrahepatic lesions. Also various types of laparoscopic hepatectomies are being performed in many centers. Some reports about the safety of laparoscopic parenchymal dissection of the liver have been published. In this study, we reported our experiences of laparoscopic left hepatectomies in patients with an intrahepatic duct (IHD) stone with recurrent pyogenic cholangitis (RPC), and investigated whether the total laparoscopic parenchymal dissection is as safe as open surgery. METHODS: From April 2008 to December 2010, 25 patients had been admitted for left IHD stones with RPC. Preoperatively, the type of surgery was decided with the intention of treating each patient. Initially 10 patients underwent a laparoscopy-assisted left hepatectomy and the next 15 patients underwent total laparoscopic left hepatectomy as our experience grew. Demographics, peri- and postoperative results were collected and analyzed comparatively. RESULTS: The mean age, gender ratio, preoperative American Society of Anesthesiologists (ASA) score, accompanied acute cholangitis and biliary pancreatitis, and the number of preoperative percutaneous transhepatic biliary drainage (PTBD) inserted cases were not different between the two groups who had undergone laparoscopy-assisted and totally laparoscopic left hepatectomy. The operation time, intraoperative transfusions and postoperative complications also showed no difference between them. The postoperative hospital stay did not show a significant difference statistically. CONCLUSIONS: In this study, we concluded that a laparoscopic left hepatectomy can be adapted to the patients with a left IHD stone with RPC. Also laparoscopic parenchymal dissection is safe and equivalent to an open procedure.